2015
DOI: 10.1097/mpg.0000000000000616
|View full text |Cite
|
Sign up to set email alerts
|

Surgery and Postoperative Recurrence in Children With Crohn Disease

Abstract: In this large cohort of children with CD studied for >10 years postoperatively, we found a high postoperative recurrence rate of disease and a frequent need for >1 intestinal resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 37 publications
0
34
0
2
Order By: Relevance
“…34 In a Danish cohort (n=115 children with Crohn's disease), the clinical recurrence rate after surgery was 50% at one year and 77% at 10 years. 120 In a retrospective review (n=81 children), recurrence of Crohn's disease was related to younger age at resection, and the likelihood of a second surgery was related to disease site and occurrence of operative complications at with PIBD. Awareness of the potential for mental health problems is key, and routine inclusion of a psychosocial evaluation is important.…”
Section: Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…34 In a Danish cohort (n=115 children with Crohn's disease), the clinical recurrence rate after surgery was 50% at one year and 77% at 10 years. 120 In a retrospective review (n=81 children), recurrence of Crohn's disease was related to younger age at resection, and the likelihood of a second surgery was related to disease site and occurrence of operative complications at with PIBD. Awareness of the potential for mental health problems is key, and routine inclusion of a psychosocial evaluation is important.…”
Section: Surgerymentioning
confidence: 99%
“…121 Postoperative azathioprine did not decrease the rate of recurrence after surgery. 120 In an open label randomized trial including patients with Crohn's disease from 12 to 65 years of age (n=31), early intervention with infliximab monotherapy (compared with no infliximab) prevented clinical, serological, and endoscopic Crohn's disease recurrence following ileocolic resection. 122 Decision making regarding colectomy in children should take into consideration the toxicity of prolonged use of drugs, QOL, and self image, as well as functional outcomes and, in female patients, fertility after pouch procedures.…”
Section: Biologicsmentioning
confidence: 99%
“…In contrast, a prospective observational study concerning the long‐term outcome of conservative surgery for small bowel CD reported that immunomodulator treatment failed to reduce the risk of reoperation . Also, a recent study showed that postoperative azathioprine therapy had no influence on decreasing the rate of SR or the time to second resection among pediatric CD patients . These studies had inconsistent conclusions on the influence of TPs on SR.…”
Section: Discussionmentioning
confidence: 99%
“…Even if the clinical symptoms are relieved after surgical resection of intestine, bowel inflammation remains and clinical situations requiring further operation frequently occur. Other authors reported that cumulative clinical recurrence rates in pediatric patients at 1 year, 5 years and 10 years were 50%, 73% and 77%, respectively [12]. Consequences of bowel damage during surgery can accumulate with time and can result in digestive dysfunction in the long run [13].…”
Section: Roles Of Surgery In CDmentioning
confidence: 99%
“…An appreciable number of patients experience recurrence despite surgery. Danish data of 115 pediatric CD patients who had surgery chronicled that 50% and 73% showed clinical recurrence at 1 year and 5 years, respectively [12]. If endoscopic recurrence is included, the rate of postoperative recurrence becomes much higher [39].…”
Section: Post-operative Management Of CDmentioning
confidence: 99%